Influence of metal oxide (V2O5) in recycled waste materials for advanced durable construction technology. (20th May 2018) - Sarkar, Manas; Maiti, Moumita; Malik, Muhammad Akbar; Xu, Shilang; Li, Qinghua; Mandal, Saroj
Highlights: Flyash-V2 O5 has been sintered at different temperatures. The 5% V2 O5 reduces the mullitization temperature < 1000 o C. Building composites are prepared by using sintered Flyash-V2 O5 and alkali activator. Composite exhibits significantly higher mechanical strengths and better durability. Nano-mullite phases increase the strength and durability of building composite. Abstract: For replacement of Portland cement as well as advancement of concrete technology, the low calcium based fly ash with alkali activators plays a significant role as cementitious material in current scenario. As efficacy of fly ash requires very high temperature (≥1400 °C) activation, alternative approach of fly-ash with addition of 5% vanadium pentoxide (V2 O5 ) has been established for mullitization process at lower temperature (≤1000 °C) in this present exertion. The sintered fly ash has been used along with alkali activator for developing the construction composite at ambient temperature. Strength measurement, Ultrasonic pulse velocity, Chloride ion permeability, water absorption and sulphate resistant tests reveal that the V2 O5 assimilated fly-ash based geopolymer structures possess higher mechanical strengths and durability. The microstructural studies (FESEM, EDS, XRD, FTIR) of the samples confirm the needle shaped nano sized mullite formation at 1000 °C temperature in its matrices. Thermal behaviour of the V2 O5 based fly-ash depicted the synthesized nanoparticle was exothermic in reaction. The investigation demonstrates the formation of needle shaped mullite helps to enhance durability with higher bond strength of the composite structure and a new approach to utilize/recycle the vast resources of fly-ash with lower temperature requirement as an effective cementitious-based engineering materials.